Characterization of HDPE /polyamide 6/ nanocomposites using scanning-and transmission electron microscopy - Erdmann, Eleonora (2007)
Preparation and morphology of high density polyethylene (HDPE)/ polyamide 6 (PA 6)/modified clay nanocomposites were studied. The ability of PA 6 in dispersing clays was used to prepare modified delaminated clays, which were then mixed with HDPE. Mixing was performed using melt processing in a torque rheometer equipped with roller rotors. After etching the materials with boiling toluene and formic acid at room temperature, the morphology was examined by SEM analyses, showing that the PA 6 formed the continuous phase and HDPE the dispersed phase. X-ray diffraction patterns show that the (001) peak of the clay is dramatically decreased and shifted to lower angles, indicating that intercalated/exfoliated nanocomposites are obtained. TEM analyses confirmed the typical structure of exfoliated nanocomposites. A scheme for the mechanism of exfoliation and/or intercalation of these HDPE /PA 6/ /organoclay nanocomposites is proposed. Copyright © 2007 WILEY-VCH Verlag GmbH & Co. KGaA.